Fungal metabolite (+)-terrein suppresses IL-6/sIL-6R-induced CSF1 secretion by inhibiting JAK1 phosphorylation in human gingival fibroblasts. Issue 11 (November 2018) - Yamamoto, Satoshi; Omori, Kazuhiro; Mandai, Hiroki; Nakayama, Masaaki; Nakagawa, Saki; Kobayashi, Hiroya; Kunimine, Tadashi; Yoshimura, Hiroshi; Sakaida, Kyosuke; Sako, Hidefumi; Ibaragi, Soichiro; Yamamoto, Tadashi; et al.
Abstract: Control of bacterial infection-induced inflammatory responses is one of the effective therapeutic approaches of periodontal diseases. Natural products such as lipid mediators and metabolites from microorganisms have been used for decreasing inflammation. We previously reported that (+)-terrein inhibited activation of STAT3 and ERK1/2 in interleukin-6 (IL-6) signaling cascade, leading to prevent vascular endothelial growth factor (VEGF) secretion in human gingival fibroblasts (HGFs). However, little is still known about the role of (+)-terrein on inflammatory responses. In this study, we provided the possibility of novel action that (+)-terrein inhibits activation of Janus-activated kinase 1 (JAK1), which has a central function in IL-6 signaling cascade, and alters expression of mRNAs and proteins induced by IL-6/soluble IL-6 receptor (sIL-6R) stimulation in HGFs. First, we performed PCR array to examine IL-6/sIL-6R-induced mRNA expression, and then expression of mRNA and protein of colony stimulating factor-1 (CSF1) and VEGF were clearly determined by quantitative RT-PCR and ELISA, respectively. Treatment with (+)-terrein suppressed expression of mRNA and protein of CSF1 and VEGF by IL-6/sIL-6R stimulation. Next, to test the effect of (+)-terrein on IL-6/sIL-6R signaling cascade, we demonstrated whether (+)-terrein affects phosphorylation of JAK1 and its downstream proteins, Akt and SHP-2. Western blotting revealed that (+)-terrein inhibited IL-6/sIL-6R-induced phosphorylation of JAK1, Akt, and SHP-2. Therefore, (+)-terrein suppresses IL-6/sIL-6R-induced expression of CSF1 and VEGF via inhibition of JAK1, Akt, and SHP-2. Based on our results, we suggest that (+)-terrein is a candidate compound for anti-inflammatory effect associated with IL-6 signaling.